2017
DOI: 10.1016/j.ijsu.2017.05.062
|View full text |Cite
|
Sign up to set email alerts
|

A novel surgical strategy for secondary hyperparathyroidism: Purge parathyroidectomy

Abstract: PPTX involves comprehensive resection of supernumerary and ectopic parathyroid tissues, which may provide a more permanent means of reducing PTH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…[811,20] In the majority of studies, ectopic thymic parathyroids are almost always inferior and the incidence is reported as between 18%–28%. [5,811,16,20] In our study, we detected 18 parathyroids (15%) in the thyrothymic ligament.…”
Section: Limitationssupporting
confidence: 49%
See 1 more Smart Citation
“…[811,20] In the majority of studies, ectopic thymic parathyroids are almost always inferior and the incidence is reported as between 18%–28%. [5,811,16,20] In our study, we detected 18 parathyroids (15%) in the thyrothymic ligament.…”
Section: Limitationssupporting
confidence: 49%
“…In a recent study, a total success in nine cases with SHPT was achieved with a novel surgical method termed “purge parathyroidectomy,” a more extensive method than the classical TPTx + TTLx. [16] However, this technique has not been tested in other studies and a similar success has yet to be repeated. When we look at the literature, the percentage of cases where four glands are resected together is reported as between 72% and 98.5% according to the series.…”
Section: Discussionmentioning
confidence: 99%
“…In our approach of m-TOEPVA, we modified the purge methods 27 to the transoral access. After transection of the upper pole of the thyroid, we favor seeking and identifying the RLN and protecting the nerve first.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to parathyroid tissue, the hypothalamus and thymus also express PTH mRNA. During embryonic development, ectopic or supernumerary parathyroid glands may be formed ( 57 ), and the incidence of ectopic parathyroid glands in SHPT patients is 26%. In addition, the number of parathyroid glands is variable, with patients typically presenting with 3 to 8 parathyroid glands ( 1 ).At most ectopic parathyroid glands are found in the thymus, so thorough neck exploration is necessary to reduce the risk of postoperative recurrence and reoperation ( 58 ).…”
Section: Treatment For Hptmentioning
confidence: 99%
“…This involves complete removal of the thyroid cartilage, bilateral carotid sheaths, the fibrofatty tissue around the innominate artery, and complete removal of the parathyroid glands. It has achieved a more durable and reliable effect in terms of controlling PTH levels ( 57 ).…”
Section: Treatment For Hptmentioning
confidence: 99%